2009
DOI: 10.1002/j.0022-0337.2009.73.6.tb04753.x
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Dental Students’ Knowledge of and Attitudes Towards HIV/AIDS Patients

Abstract: Dental treatment procedures frequently involve blood and saliva that may be contaminated with HIV. The purpose of this cross-sectional survey was to assess Iranian dental students' knowledge of and attitudes towards HIV/AIDS patients. In 2008, a fifty-three-item self-administered questionnaire was conducted on all 750 dental students who participated in the 10 th Dental Student Congress in Isfahan, Iran. The overall response rate to the questionnaire was 60.7 percent. The total mean knowledge and attitudes sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
83
4
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(132 citation statements)
references
References 17 publications
36
83
4
9
Order By: Relevance
“…This finding might indicate the misconception of the disease pathogenicity or the social stigma associated with HIV‐infected people. These results conform to dentists’ attitude towards patients with HIV/AIDS in published reports from other regions in the world. In a similar study in Jordan, a country that is considered to be the closest in culture and beliefs to Palestine, 45% of the respondent dentists were willing to treat HBV‐infected patients compared with 15% who agreed to provide care for HIV‐infected patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding might indicate the misconception of the disease pathogenicity or the social stigma associated with HIV‐infected people. These results conform to dentists’ attitude towards patients with HIV/AIDS in published reports from other regions in the world. In a similar study in Jordan, a country that is considered to be the closest in culture and beliefs to Palestine, 45% of the respondent dentists were willing to treat HBV‐infected patients compared with 15% who agreed to provide care for HIV‐infected patients.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, increasing the awareness of dental professionals about how to deal with patients with blood‐borne diseases and improving infection‐control measures at dental clinics might play a more positive role in improving dentists’ attitude and confidence towards treating those patients. The literature showed that high awareness of the disease process and the measures that minimise the risk of transmission increases dentists’ willingness to treat those patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most participants said that Kaposi's sarcoma (89.5% of women and 90% of men) and oral candidiasis (85.2% of women and 82.5% of men) are oral signs of HIV/ AIDS. Those diseases seem to be the most known by dentists as related to HIV/ AIDS, as it was demonstrate by other studies [12,20,21]. In Oliveira et al [20], 92.5% e 90.3% of participants said that Kaposi's sarcoma and oral candidiasis, respectively, are oral manifestations of HIV/ AIDS.…”
Section: Discussionmentioning
confidence: 64%
“…for necrotizing ulcerative gingivitis, 85% for hairy leukoplakia, 81% for Herpes zoster and major aphthous and 75% for salivary gland infection. In Sadeghi and Hakimi [12] work, several lesions were pointed out as associated to HIV/ AIDS, such as oral candidiasis (98%), Kaposi's sarcoma (94%), necrotizing ulcerative gingivitis (91%), severe periodontitis (88%), cytomegalovirus (87,6%), gingivitis (83%), xerostomia (83%), hairy leukoplakia (82%), salivary gland infection (81%), herpes zoster (79%), herpes simplex (77%) and lichen planus (54%). Interestingly, despite oral herpes simplex being an oral pathognomonic marker of HIV, current results showed a low rate of positive answers relating these lesions to HIV+.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation